Dopamine D(2)-Like Receptors and Behavioral Economics of Food Reinforcement - Soto, Paul L (Neuropsychopharmacology, 2016)
Previous studies suggest dopamine (DA) D(2)-like receptor involvement in the reinforcing effects of food. To determine contributions of the three D(2)-like receptor subtypes, knockout (KO) mice completely lacking DA D(2), D(3), or D(4) receptors (D(2)R, D(3)R, or D(4)R KO mice) and their wild-type (WT) littermates were exposed to a series of fixed-ratio (FR) food-reinforcement schedules in two contexts: an open economy with additional food provided outside the experimental setting and a closed economy with all food earned within the experimental setting. A behavioral economic model was used to quantify reinforcer effectiveness with food pellets obtained as a function of price (FR schedule value) plotted to assess elasticity of demand. Under both economies, as price increased, food pellets obtained decreased more rapidly (ie, food demand was more elastic) in DA D(2)R KO mice compared with WT littermates. Extinction of responding was studied in two contexts: by eliminating food deliveries and by delivering food independently of responding. A hyperbolic model quantified rates of extinction. Extinction in DA D(2)R KO mice occurred less rapidly compared with WT mice in both contexts. Elasticity of food demand was higher in DA D(4)R KO than WT mice in the open, but not closed, economy. Extinction of responding in DA D(4)R KO mice was not different from that in WT littermates in either context. No differences in elasticity of food demand or extinction rate were obtained in D(3)R KO mice and WT littermates. These results indicate that the D(2)R is the primary DA D(2)-like receptor subtype mediating the reinforcing effectiveness of food.